Evidence that Enzyme Processivity Mediates Differential Aβ Production by PS1 and PS2 - A. Pintchovski, Sean; B. Schenk, Dale; S. Basi, Guriqbal (Current Alzheimer Research, 2013)
The γ-secretase complex cleaves the carboxy-terminal 99 residue (C99) fragment of the amyloid precursor protein (APP) to generate the amyloid-β (Aβ) peptide. The catalytic activity of this complex is mediated either by the presenilin- 1 (PS1) or the presenilin-2 (PS2) subunit. In vitro and in vivo studies have demonstrated that PS1-containing complexes generate more total Aβ product than PS2-containing complexes, indicating greater cleavage activity by PS1- containing γ-secretase complexes at the APP γ-site. However, it remains untested whether γ-secretase cleavage at the APP ε-site, which precedes γ-site cleavage and produces the physiologically active APP intracellular domain (AICD), follows the same rule. Using a novel Swedish APP-GVP substrate to facilitate the parallel detection of Aβ and AICD products from PS1-/-/PS2-/- cells co-transfected with either PS1 or PS2, we observed that while PS1 generates more total Aβ product than PS2, consistent with published reports, PS1 and PS2 unexpectedly generate equal amounts of AICD product. We also observed that PS1 and PS2 produce equivalent amounts of Notch intracellular domain (NICD), indicating equal cleavage activity at the Notch S3-site (the corollary of the APP ε-site). Our findings suggest that processivity differences between PS1 and PS2 underlie the differential production of Aβ peptide. Taken together these findings offer novel insights into γ- secretase biology and have important implications for therapeutically targeting γ-secretase.
Keywords: APP-GVP substrate